Juegos pedagógicos y su influencia en el desarrollo socio afectivo en los niños de cuatro años de educación inicial de la Unidad Educativa Francisco Huerta Rendón - Peñafiel Jaramillo, Jennifer Lilibeth (2023)
Pedagogical games have a significant impact on the socio-affective development of preschool children, therefore, it is very important to analyze this topic. These activities not only favor academic learning, but also promote social, emotional and communicative skills. Through interaction with their peers in play activities, children learn to work as a team, share and resolve conflicts peacefully. The games provide a safe space to express emotions and develop empathy for others. The study was conducted at the "Francisco Huerta Rendon" Educational Unit. The objective is to determine the influence of pedagogical games on socio-affective development. The methodology is the following: qualitative approach, non-experimental design, descriptive and correlational scope. The methods used are: analytical, synthetic, inductive, deductive and historical. The sample used corresponds to 28 students and 3 teachers.